A Survey of a Residential Load Profile for Demand Side Management Systems - Elma, Onur; Selamogullar, Ugur S. (IEEE, 2017)
Management of residential electricity consumption is one of the important issues for energy efficiency and future smart grid systems since residential demand constitutes large percent of overall electrical energy consumption. Therefore, demand side management systems, named as home energy management systems at the residential level, are being implemented under the new smart grid concept. Analyzing the performances of home energy management systems requires generating different realistic residential demand profiles since the residential demand is highly complex comprising several factors such as occupancy, climate, user preferences, and types of appliances. This study provides the result of a survey analysis that can be used to generate such realistic residential demand profiles. In the survey, information about the user preferences for appliance use time and duration and about user will to be part of a demand control program are obtained. Results of the survey together with experimentally measured power values of appliances are used to produce sample representative load profiles for a weekday and for a weekend. These load profiles can be used in the evaluation of home energy management systems.
Keywords: residential loads profiles; home energy management; demand side management; smart grid; ENERGY-CONSUMPTION; SMART HOME; OPTIMIZATION; APPLIANCES; SCHEME; Energy & Fuels; Engineering